It “Made Me Who I Am”: Using Interpretive and Narrative Research to Develop a Model for Understanding Associate Deans’ Application and Development of Academic Identity - Stovin, Derek (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
Interpretive and narrative research approaches, the experiences of academic administrators other than deans, chairs, and presi-dents, and academic identity work beyond graduate students and beginning professors are all areas that are underrepresented in the literature on higher educational administration. This article builds on recent narrative research by applying higher educational admin-istrative theories as interpretive lenses to propose a model for helping to understand the development and application of associate deans’ academic identities. Among the findings were that academic identities helped explain associate deans’ approaches to their roles, their views of their surrounding organizations, and their reasons for assuming the role. Further, the associate deans who partic-ipated in this research did not experience their transition to the role as an identity crisis in the ways typically described and assumed by higher educational leadership scholars. Instead, they drew upon their well-established academic identities and, in keeping with the nascent research on academic identity work, were intentional in their efforts to maintain their academic identities.